2022
DOI: 10.1088/1755-1315/998/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma activated water (PAW) in maintaining the quality of cherry tomatoes

Abstract: Recently consumer demand of fresh fruits has been increased because public are more aware with their health. Fruits are often consumed raw, and that increase the chances of people being infected by pathogenic bacteria. This problem encourages the need to find new methods to maintain the quality and hygiene of fruits. Preservation methods that are often used today have many disadvantages, for example the use of temperature-based method that could possibly damage the texture and nutrient of the fruits. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…However, it is necessary to determine the optimal HT for achieving maximum inactivation efficiency with minimum exposure to PAW, as the reactive species present in PAW can reduce the quality of the fresh produce. Many studies recommend the duration of treatment to be restricted to <5 min for minimal variation in quality [ 21 , 22 ]. The Ministry of Food and Drug Safety in Korea also suggests immersion for 5 min, based on the sodium hypochlorite treatment duration, as a guideline for the use of disinfectants in food.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is necessary to determine the optimal HT for achieving maximum inactivation efficiency with minimum exposure to PAW, as the reactive species present in PAW can reduce the quality of the fresh produce. Many studies recommend the duration of treatment to be restricted to <5 min for minimal variation in quality [ 21 , 22 ]. The Ministry of Food and Drug Safety in Korea also suggests immersion for 5 min, based on the sodium hypochlorite treatment duration, as a guideline for the use of disinfectants in food.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have shown that PAW could inactivate foodborne pathogens inoculated on fresh produce, such as strawberries, grape berries, tomatoes, and mushrooms, and maintain their quality [ 15 , 18 , 19 , 20 ]. Studies have reported that PAW can also effectively inactivate microbes commonly present on the surface of fresh produce in nature, including aerobic bacteria, yeasts, and molds, helping to increase the shelf-life of fresh produce and ensuring safety and quality during storage [ 21 , 22 , 23 , 24 ]. However, there are limited reports on the applicability of PAW as a wash solution in the fresh produce industry and much less information on whether the application of PAW, effective against a broad range of pathogens, is safe for human health.…”
Section: Introductionmentioning
confidence: 99%
“…It is accepted that the microbial inactivation of PAW is due to a combination of its RONS and low pH. The ORP of PAW could also be an important factor affecting PAW inactivation (Kasih et al, 2022). Bai et al (2020) noted that the initial concentration of bacteria affects the bacterial resistance to PAW treatment, revealing that the higher the bacterial load, the lower the inactivation rate.…”
Section: Microbial Inactivation By Pawmentioning
confidence: 99%
“…It is accepted that the microbial inactivation of PAW is due to a combination of its RONS and low pH. The ORP of PAW could also be an important factor affecting PAW inactivation (Kasih et al., 2022). Bai et al.…”
Section: Microbial Inactivation By Pawmentioning
confidence: 99%
“…Around 6 log CFU/g reduction in Escherichia coli populations was observed in PAW treatment (Perinban et al., 2022), and populations of E. coli and Salmonella on coriander, peppermint, asparagus, okra, ginger, and lemongrass were decreased by more than 1 log reduction after washing with MNB (Mahakarnchanakul et al., 2015). Furthermore, various studies demonstrated the effects of AWS to maintain the quality of melons (Le Nguyen et al., 2019), cherry tomato (Kasih et al., 2022), and carambola fruit (Zhang et al., 2023).…”
Section: Introductionmentioning
confidence: 99%